Secondary Chronic Immune Thrombocytopenia in Diffuse Large B-cell Lymphoma: A Rare Case Report - Putri Vidyaniati; Fransisca Fransisca; Kiki Akhmad Rizki; Amaylia Oehadian (Faculty of Medicine Universitas Padjadjaran, 2022)
Objective: To present a case of rare secondary chronic immune thrombocytopenia in diffuse large B-cell lymphoma.Methods: A case of secondary ITP associated with diffuse large B-cell lymphoma (DLBCL) in a 58-year-old woman suffering from hemorrhagic tendencies that was refractory to conventional treatments of ITP was reported. This case is a rarity because there are not many cases of secondary chronic ITP due to DLBCL have been reported to date.Results: A 58-year-old woman was diagnosed with ITP around 11 months before she was admitted to the Emergency Room with bleeding. Previous treatment with steroid and azathioprine was only temporarily effective. During the course of treatment, splenomegaly and lymphadenopathy were identified, but lymph node biopsy was delayed by the thrombocytopenia. The drug was then replaced to the eltrombopag, which showed good response. However, the patient had to undergo splenectomy because of the mechanical effect of splenomegaly, with the biopsy result showed DLBCL. Immune thrombocytopenia then went into a complete remission after splenectomy.Conclusion: In cases of ITP that are refractory to conventional treatments, a thorough search for secondary ITP might be helpful, even if no underlying disorder is detected at the initial presentation.